2015
DOI: 10.1186/s41043-015-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive breast feeding is the strongest predictor of infant survival in Northwest Ethiopia: a longitudinal study

Abstract: Despite the overall national success in reducing infant mortality rate in Ethiopia, infant mortality rate is still high in northwest Amhara region. This study is conducted in one of the high mortality areas with the aim of identifying risk factors that are associated with infant mortality in Northwest Amhara Region, Ethiopia. A prospective open cohort study involving 1752 infants (1472.4518 person years of follow-up) was undertaken from November 2009 to August 2011. Kaplan-Meier Survival analysis was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 19 publications
5
52
2
4
Order By: Relevance
“…In the study in Dabat, family income was not a significant predictor for EBF practice [19], while it was statistically associated with EBF according to a study done in Awi Zone, northwest Ethiopia [21]. …”
Section: Introductionmentioning
confidence: 99%
“…In the study in Dabat, family income was not a significant predictor for EBF practice [19], while it was statistically associated with EBF according to a study done in Awi Zone, northwest Ethiopia [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Mothers who did not use soap for hand washing had higher infant death than those who used soap [39]. Infants whose mothers were not washing their hands with soap after visiting toilet and before feeding child had high mortality rate than their counterparts [IRR = 4.61, 95% CI: (2.24, 9.48)] [32]. In terms of etiological fractions, a greater number of U5M could be ascribed to parental compared to environmental conditions, with relatively more infants being affected than children [19].…”
Section: Hygiene Practicementioning
confidence: 99%
“…The likelihood of death among children who were not breastfed was 6 times higher compared to their counterparts [23]. Infants not exclusively breastfed and given breast milk after 24 hours of birth had higher mortality than their counterparts with IRR = 7.86, 95% CI: (5.11, 12.10) and IRR = 4.84, 95% CI: (2.94, 7.99), respectively [32]. A community based study done using verbal autopsy method in Gondar revealed that malnutrition is one of the causes of childhood mortality [33].…”
Section: Breastfeedingmentioning
confidence: 99%
“…Thus, the discussion of these variables can reveal cultural trends of a population group as regards BF (SILVA, 2013;BIKS, 2015;SALUSTIANO, 2012).…”
Section: Discussionmentioning
confidence: 99%